The New Complex-Valued Wavelet Neural Network - Sufang Li; Mingyan Jiang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
A new complex-valued wavelet neural network is proposed in this paper, by introducing a modified complex-valued back propagation algorithm, in which a new error function is to be minimized by the algorithm. The improvement performance is further confirmed by the simulation results, which show that the modified algorithm is simpler than the conventional algorithm, and has better convergence, better stability and faster running speed.